Prospects for cooperation between the financial corporation and companies, working in the field of digital technologies - V. S. Efremov; A. S. Pilishvili (Управление)
The problems, associated with the development of new digital technologies, which, in turn, have an impact on the activities of large financial institutions of the Russian Federation, have been examined in the article. The aim of the study is to analyze the current situation in the economy, related to the growth of the market for digital products, their integration into the existing model of providing financial services to clients, as well as finding solutions to the joint activities of financial corporations and financial and technological companies. The definitions and main activities of financial corporations and fintech startups have been given in the article. The advantages and disadvantages of a large financial corporation and developing companies, operating in the field of digital technologies, as well as the positive results of combining their resources, have been highlighted. Positive examples of world experience in cooperation between the two types of these organizations and the attitude of the main regulator of the Central Bank of Russia to the development and implementation of financial technologies in the country’s economy have been adduced.The problems and opportunities of high competition in the struggle for the modern consumer, which lead to the rapid development of the entire financial industry market, have been analyzed. The results of the study have showed, that every day, worldwide, fintech companies test a significant number of digital products, various open architecture tools, methods of transferring information through blockchain technologies, and optimize and integrate into the existing systems new client base programs, that completely change the main business processes of large enterprises and have a significant impact on the main consumer - a person. This indicates the need for further research aimed at studying and analyzing the integration of financial corporations with technology companies, changing the existing business model, finding new approaches to the modern consumer and creating a new organization development strategy in the digital economy of the country.